2004
DOI: 10.1158/1078-0432.ccr-03-0462
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Growth Factor Receptor, c-MET, β-Catenin, and p53 Expression as Prognostic Indicators in Stage II Colon Cancer

Abstract: Purpose: Through the use of molecular markers, it may be possible to identify aggressive tumor phenotypes and tailor therapies to treat them. This approach would be particularly useful for stage II colon cancer. The purpose of this study was to define the prognostic value of epidermal growth factor receptor (EGFR), c-MET, ␤-catenin, and p53 protein expression in TNM stage II colon cancer using tissue microarray technology.Experimental Design: In this study, we retrospectively analyzed, resected, and otherwise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
124
0
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(141 citation statements)
references
References 39 publications
13
124
0
4
Order By: Relevance
“…As these two tests may yield a lower number of positive cases, one could argue that some of the negative cases of this report could have been positive if they were tested by Ventana 3C6 or the Zymed test used in our current study. Four antibodies were used in the recent studies of EGFR expression and according to our study, showed that they were not equivalent in terms of the percentage of positive cells (Table IV) (10)(11)(12)(13)(14)(15)(16).…”
Section: Discussionmentioning
confidence: 89%
“…As these two tests may yield a lower number of positive cases, one could argue that some of the negative cases of this report could have been positive if they were tested by Ventana 3C6 or the Zymed test used in our current study. Four antibodies were used in the recent studies of EGFR expression and according to our study, showed that they were not equivalent in terms of the percentage of positive cells (Table IV) (10)(11)(12)(13)(14)(15)(16).…”
Section: Discussionmentioning
confidence: 89%
“…25,67 Furthermore, previous studies have provided evidence for the prognostic value of MET protein expression in the early stages of carcinoma progression. 68,69 In this study the majority of patients had metastatic disease and they all received the appropriate chemotherapy although their access to EGFR-or VEGF-targeted therapy was not always based on molecular biomarker selection; therefore, the data reported herein highlight the value of MET expression in metastases as a biomarker that might be used to select advanced colorectal cancer patients who could benefit from targeted therapies.…”
Section: Discussionmentioning
confidence: 95%
“…Although individuals at an early stage of colorectal cancer are excluded from adjuvant chemotherapy because tumor resection is potentially curative, 20% to 30% of such cases present recurrence of the disease. This suggests that the anatomopathological staging in itself is incapable of guaranteeing the patient's prognosis (24) . Therefore, investigation of molecular markers is important for evaluating the prognosis, and for allocating individuals to appropriate treatment protocols.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular markers may be the basis for decision-making of lower cost and greater precision, for prognoses and appropriate adjuvant therapies. Over recent years, the major focus within colorectal cancer research has been on searching for molecular markers that provide a prognosis and identify population types for specific treatment regimens (24) .…”
Section: Discussionmentioning
confidence: 99%